Cover Image, Volume 140, Issue 22. Issue 22 (1st May 2023) - Tavakoli, Mohamadreza; Labbaf, Sheyda; Mirhaj, Marjan; Salehi, Saeideh; Seifalian, Alexander Marcus; Firuzeh, Mahboubeh
Abstract : The cover image created by Sheyda Labbaf shows that carbohydrates and proteins are the family of natural polymers that are widely used in wound healing. Chitosan, as a carbohydrate, has the most clinical application as it is readily available and affordable, and has shown excellent antibacterial activity. Among proteins, keratin can be an option with similar characteristics, however, Keratin has not yet found great clinical compared with chitosan. This review covers the most widely studied natural polymers for potential applications in wound dressings. DOI: 10.1002/app.53910